Relationship between Age, Working Memory and Cognitive Reserve Capacity - Martín Valle, Belén (2023)
Objective. In this work, it was intended to show the relationship between age, verbal and visuospatial working memory, and cognitive reserve in people over 40 years old. Method. The sample was composed of 50 people from 40 years old onwards, of both genders and without associated pathologies. For data collection, the INECO frontal screening subtests and the Cognitive Reserve Questionnaire (CRC) were administered. Results. In this sample, it was possible to determine that the greater the cognitive reserve capacity a person has, the greater their working memory capacity will be, specially the visuospatial type.